2012
DOI: 10.2478/v10222-011-0048-y
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Phenolic Compounds Isolated from Cocoa, Green Tea and Strawberries in Hank’s Balanced Salt Solution under Cell Culture Conditions.

Abstract: The study analysed the stability of polyphenols present in extracts isolated from cocoa, green tea and strawberries in Hank's Balanced Salt Solution buffers. The extracts were incubated under conditions commonly used for intestinal absorption experiments with human epithelial cells. The polyphenols were analysed with HPLC-DAD-FLD-MS method. The concentrations of most of the polyphenols monitored changed during 2 h of incubation. The fl avan-3-ols of cocoa exhibited similar stability and all were more stable at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…The catechins are the major bioactive components in tea extracts, but unfortunately, they are unstable under various experimental conditions. Therefore, several investigations have been performed to assess the stability of catechins such as EGCG, EC, ECG, and EGC in different buffers . Efforts have also been made to find ways to stabilize EGCG under the assay conditions .…”
Section: Resultsmentioning
confidence: 99%
“…The catechins are the major bioactive components in tea extracts, but unfortunately, they are unstable under various experimental conditions. Therefore, several investigations have been performed to assess the stability of catechins such as EGCG, EC, ECG, and EGC in different buffers . Efforts have also been made to find ways to stabilize EGCG under the assay conditions .…”
Section: Resultsmentioning
confidence: 99%
“…46 They found that most of the polyphenols decomposed during 2 h of incubation. EGCG and EGC were very vulnerable in HBSS both at pH 6.5 and 7.4; their specific molecular structure was discussed to be responsible for this phenomenon.…”
Section: ■ Discussionmentioning
confidence: 98%
“…EGCG and EGC were very vulnerable in HBSS both at pH 6.5 and 7.4; their specific molecular structure was discussed to be responsible for this phenomenon. 46 The flavan-3-ols from cocoa were more stable at pH 6.5 than at pH 7.4. The major oxidative products of EGCG in McCoy's 5A culture media were theasinensin and its dimer.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our previous study revealed a non-enzymatic release of EA from sanguiin H-6 and other ellagitannins present in the strawberry extract (Kosiń ska et al, 2012). EA was reported to be liberated from ellagitannins of other fruits, e.g.…”
Section: In Vitro Gastrointestinal Digestion Of Strawberry Extractmentioning
confidence: 98%